Carbon nanotube-based biomaterials for orthopaedic applications. Issue 40 (16th September 2020) - Aoki, Kaoru; Ogihara, Nobuhide; Tanaka, Manabu; Haniu, Hisao; Saito, Naoto
Abstract : Carbon nanotubes can enhance the functionality of orthopedic applications. Abstract : Carbon nanotubes (CNTs) are cylindrical tubular nanomaterials made of carbon with excellent electrical conductivity, thermal conductivity, and mechanical strength. The material is applied to improve performance in various industrial products. CNTs have been widely researched and developed as biomaterials that can offer high function, performance, and durability in orthopedic applications. However, the use of CNTs as biomaterials must be administered with caution, as the fibrous nanomaterial may be carcinogenic due to its similar size and shape to asbestos. In this review article, we examine the potential clinical application of CNTs in orthopedic surgery. We first provide an overview of biocompatibility and carcinogenicity studies of CNTs with a focus on their effects on the bone, joint, and respiratory system. Furthermore, we introduce CNT-based biomaterials for orthopedic applications that have been reported in the literature, including scaffolds for bone and cartilage regeneration, composites that enhance the performance of biomaterials, CNT coatings, and devices for treating musculoskeletal tumors.